INFLUENCE E-SERVICE QUALITY, PERCEIVED VALUE AND CUSTOMER SATISFACTION TO CUSTOMERS E-COMMERCE LOYALTY SHOPEE FOR THE PEOPLE OF LHOKSEUMAWE - Putri Patresia; T. Zulkarnaen; JuliMursyida; M.Subhan (RADJA PUBLIKA, 2024)
Market developments in the e-commerce business make it easy for consumers to fulfill almost all their needs online, ranging from clothing, electronic equipment, cosmetics, even plane tickets and hotel reservations. One of the e-commerce websites in Indonesia is Shopee, an e-commerce startup, Shopee is a big player in e-commerce, of the many marketplaces present in Indonesia, Shopee is one of the many parties taking advantage of this opportunity by enlivening the mobile segment marketplace through their mobile application can make buying and selling transactions easier via mobile devices. The development of the times has resulted in more and more marketplaces emerging. This research aims to determine the influence of e-service quality, perceived value and customer satisfaction on Shopee e-commerce customer loyalty in the Lhokseumawe City Community. This type of research is quantitative research with the community population in Lhokseumawe City. Respondents totaled 100 people, taken using purposive sampling technique. The data source comes from primary data obtained through distributing questionnaires. The data analysis techniques used are descriptive analysis methods and multiple linear regression analysis, classical assumption tests, instrument tests (validity and reliability), hypothesis tests and coefficient of determination as well as correlation tests and analyzed with the help of the SPSS 23.0 application program. The research results show that simultaneously perceived value and customer satisfaction have a positive and significant effect on Shopee e-commerce customer loyalty in the Lhokseumawe City Community. Furthermore, e-service quality has a negative and insignificant influence on Shopee e-commerce customer loyalty in the people of Lhokseumawe City.